Personal Identity of the Artist as a Condition and Result of Creativity in Art - Nadezda Y. Mochalova (Publishing house "Sreda", 2020)
The author outlines that the essence of the problem of personal identity is formulated in the form of a dilemma: the personality must be identical to itself, because it retains the inconsistency of all experiences, actions, plans throughout the life of the individual; the personality must not be identical to itself on the basis of its inclusion in the context of changing being, which inevitably implies its internal self-change. It is noted that this dilemma involves the use of the term "identity" in two contexts: in the context of comparison (the opposite meaning of "identical" is expressed in the following terms: "other", "another", "alien", "unequal", "reverse") and in the context of development, temporality (the term "identity" becomes the opposite meaning of "changed", "impermanent", "developing"). Research methods: analysis of literature on the topic studied; comparison, descriptive method. The artist's creative identity as a dialectical process of changing the dominant forms, styles, and images is reviewed in the article. The artistic and ontological problem of self-identity of artistic personality is presented through the dialogue between "One" and "Other". The artistic reality of a work of art allows the artist to know the essence of his identity in the context of intersubjectivity. It is concluded that the paradigm that allows us to detect intersubjective conditionality of identity is the relational ontology, which represents relationships as a fundamental form of being. It is emphasized that personal identity is discursively mediated by a person's self-understanding, so hermeneutics primarily becomes the methodological space in which this research is carried out. Hermeneutics proves that self-knowledge and self-understanding of a person is an interpretive process that forms an important part of the subject's ontology. According to this methodology, personal identity is mediated by its own interpretive activity as a narrative philosophy, as a person's story about himself, and as the formation of a life story. The author is impressed by the productive idea of E.G. Trubina's research on the reflection of the individual as a creative process of self-construction in relation to the modified personal identity of the artist.